Pengaruh Komponen Risk Based Bank Rating Pada Nilai Perusahaan Perbankan - Savitri, Ketut Krisna; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
This study aims to empirically examine the effect of the risk-based bank rating component as measured by non-performing loans, loan to deposit ratio, good corporate governance, return on assets and capital adequacy ratio on the value of banking companies listed on the Indonesia Stock Exchange (BEI) Year 2013-2017. The research sample was selected using the nonprobability sampling method with a purposive sampling technique and obtained as many as 6 banking companies, so that the number of observations with a study period of 5 years was 30 observations. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that non-performing loans and loan to deposit ratios have a negative effect on the value of banking companies. Return on assets and capital adequacy ratio have a positive effect on the value of banking companies and good corporate governance does not affect the value of banking companies. Keywords : Risk Based Bank Rating;  Company Value; Banking.